Human capital and firm's propensity to relocate: do jobs follow people? - Gintare Morkute (European Regional Science Association (ERSA), 2015)
This paper examines the role that human capital plays in firm?s strategic decisions. It focuses on long-distance corporate relocations which present certain trade-offs in terms of human capital and modifies firms? relationship with the labour force. It is assessed to what extent having (an access to) employees with desired characteristics can deter firm?s relocation and to what extent the relocating firms upgrade their (access to) workforce. Based on literature analysis, three aspects of human capital are identified as creating value to the firm: 1) skill level of employees, 2) quality of job matches, characterised by firm-specificity and embeddedness of human capital, 3) accessibility of external labour force. The role of all three aspects as both keep and pull factors is tested using register data on single-plant firms in the Netherlands in 2006-2011. The results demonstrate that firms show a strong attachment to the employees and retaining labour force is an important consideration of relocating firms. Long-distance relocations are infrequent and they happen predominantly among firms that have very long commuting and hiring distances already before the relocation, which indicates low dependence on the local labour markets and enables long moves with little increase to the employees? commutes. Firms are neither kept put by having employees with high skill level nor do they use relocation to upgrade the skill level. The quality of job matches and access to external workforce affect firm?s relocation decisions, but only as keep factors. The asymmetry between their role in keeping firms put and attracting firms is indicative of footloose firms being indifferent to local differentials pertaining to human capital rather than being motivated by them. It also suggests that (access to) human capital primarily has an anchoring role as the complex relationships linking firms to both internal and external labour force cannot be easily replicated elsewhere or well estimated before the relocation. The paper is concluded by noting that in the case of firm relocation human capital differentials do not contribute to redistribution of employment; rather it is one of the forces that maintain the present job distribution. Firms are rooted due to the human capital they have; they tend not to search opportunistically for greener pastures. Skill level of the employees has no bearing on this rootedness, rather it is determined by the culture and human resource practices of the firm itself as well as by its dependence on the local labour markets. The findings suggest that in understanding how human capital creates value more attention should be paid not only to cognitive/physical/other abilities of an individual, but also the context-specific possible uses for them.
Keywords: J23; J24; R12; R30; 330; firm relocation; mobility; human capital; human resources; do jobs follow people